A cross-sectional analysis of factors associated with the teachable moment concept and health behaviors during pregnancy - Linda M. Uzan; Michelle Brust; Joyce M. Molenaar; Eva Leistra; Klarke Boor; Jessica C. Kiefte-de Jong (BMC, 2024)
Abstract Background Pregnancy is often associated with a change in health behaviors, leading some to suggest that pregnancy could be a teachable moment for lifestyle change. However, the prevalence and underlying mechanism of this phenomenon is not well understood. The aim of this study is to explore the prevalence of a teachable moment during pregnancy, the psychosocial factors that are associated with experiencing such a moment, and its association with actual health behaviors. Methods In this cross-sectional study, 343 pregnant Dutch women completed an online questionnaire. Participants reported on their intentions to change lifestyle due to pregnancy, their current health behaviors, and several psychosocial factors that were assumed to be linked to perceiving a teachable moment during pregnancy: perceived risk, affective impact, changed self-concept, and social support. Multivariable linear and logistic regression were applied to the data analysis. Results Results demonstrate that 56% of the women experienced a teachable moment based on intentions to change their health behavior. Multivariate regression analyses revealed that changed self-concept (β = 0.21; CI = 0.11-0.31), positive affect (positive β = 0.28; CI = 0.21-0.48), and negative affect (β = 0.12; CI = 0.00-0.15) were associated with higher intentions to change health behavior. Conversely, more perceived risk was associated with lower intentions to change health behavior (β=-0.29; CI = 0.31 − 0.13). Multivariate regression analyses showed a positive association between intentions to change health behavior and diet quality (β = 0.11; CI = 0.82-1.64) and physical activity (OR = 2.88; CI = 1.66-5.00). Conclusions This study suggests that pregnancy may be experienced as a teachable moment, therefore providing an important window of opportunity for healthcare professionals to efficiently improve health behaviors and health in pregnant women and their children. Results suggest that healthcare professionals should link communication about pregnancy-related health behaviors to a pregnant women's change in identity, affective impact (predominantly positive affective impact) and risk perception to stimulate the motivation to change healthy behavior positively.